(untitled) (Archaeologia Adriatica, 2009)
The spatial organization of the village of Tršci and the neighboring villages, particularly Zemunik, is analyzed in the article. Particular attention is paid to the extent of the territory, and the location of settlements and roads, leading to the conclusion that the village was formed from a former estate from late antiquity.